Pengalaman Keluarga yang Mempunyai Anak Pengguna Napza dalam Menjalani Kehidupan Bermasyarakat - Ritanti; Wiarsih, Wiwin; Asih, Imalia Dewi (Jurnal Keperawatan Soedirman, 2010)
The study explored the experiences of families who have drug and addictive substance user children in living their social lives. This study used Husserlian descriptive phenomenological design. Data was obtained through an in-depth interview and analyzed by using Colaizziï¿½s method. The identified research themes of this study are the feelings of family, stigma felt by families, coping mechanism used by families, family burden, solving the problem, support for the family and family expectations to the authority and community. The families who have drug and addictive substance user were experiencing a deep, prolonged and repeated grieving process. Moreover, some of them also felt desperate. Therefore, it was recommended for community nurse to develop and addictive substance prevention program.